2007
DOI: 10.1007/s00431-007-0513-0
|View full text |Cite
|
Sign up to set email alerts
|

What is new in ventilation strategies for the neonate?

Abstract: A large number of ventilation strategies are now available for the neonate. This review has focused on new information, that is, studies published since 2000 and the implication of their results for current clinical practice. Meta-analysis of randomised trials has demonstrated that assist control and synchronous intermittent mandatory ventilation (SIMV) shortens the duration of ventilation only if started in the recovery rather than the early stage of respiratory disease. A recent randomised trial demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…In 2006, we initiated a new mode of ventilation, namely, volume-guarantee (VG) ventilation, which reduces large tidal volumes, decreases the incidence of inadvertent hyperventilation, reduces the duration of mechanical ventilation and pneumothorax [26], and reduces proinflammatory cytokine levels [11]. Furthermore, VG decreases the expression of early inflammatory markers to a greater extent than high-frequency oscillatory ventilation [27].…”
Section: Discussionmentioning
confidence: 99%
“…In 2006, we initiated a new mode of ventilation, namely, volume-guarantee (VG) ventilation, which reduces large tidal volumes, decreases the incidence of inadvertent hyperventilation, reduces the duration of mechanical ventilation and pneumothorax [26], and reduces proinflammatory cytokine levels [11]. Furthermore, VG decreases the expression of early inflammatory markers to a greater extent than high-frequency oscillatory ventilation [27].…”
Section: Discussionmentioning
confidence: 99%
“…Use of high-frequency oscillatory ventilation (HFOV) has been evaluated as both a mode of ventilation for prophylaxis against BPD and as a rescue mode for infants in severe respiratory failure. A meta-analysis of 11 trials comparing early use of HFOV to conventional ventilation showed a modest reduction in BPD but no statistically significant effect on mortality, short-term neurologic outcomes, ICH, or PVL [26]. However, many other recent studies have provided conflicting data [27][28][29].…”
Section: Why Prevention and Treatment Have Not Worked Thus Farmentioning
confidence: 99%
“…These conflicting data are likely to be due to differences in the study populations among various studies. HFOV has also been used as a rescue mode for infants in severe respiratory failure, but the evidence that this approach can reduce BPD or improve long-term outcomes in preterm infants is not yet available [18,26].…”
Section: Why Prevention and Treatment Have Not Worked Thus Farmentioning
confidence: 99%
“…Elective HFOV has been compared with conventional ventilation in a number of trials. Meta-analyses have shown a modest reduction in BPD in survivors at term with no significant effect on neurological adverse effects such as IVH or PVL [117,118]. There have only been two randomized controlled trials examining the efficacy of rescue HFOV and only one of these has included preterm infants.…”
Section: High Frequency Oscillation Ventilationmentioning
confidence: 95%
“…HFOV may be used electively or as rescue in response to severe respiratory failure during conventional ventilation. The concept of HFOV is that tiny gas volumes, less than anatomical dead space are moved in and out at rapid rates promoting assisted gas diffusion [48,118]. In animal models HFOV appears to be a less injurious mode of ventilation.…”
Section: High Frequency Oscillation Ventilationmentioning
confidence: 99%